Strategi Peningkatan Produktivitas Lada dengan Tajar Tinggi dan Pemangkasan Intensif serta Kemungkinan Adopsinya di Indonesia - DARAS, USMAN (Perspektif, 2015)
RINGKASANLada merupakan salah satu komoditas ekspor tradisional penting Indonesia. Capaian produktivitasnya secara nasional masih rendah (< 1.0 ton/ha), di bawah produktivitas negara penghasil utama lada lain seperti Vietnam, Brazil dan Malaysia. Banyak faktor yang diperkirakan berkontribusi terhadap rendahnya produktivitas. Faktor tersebut dapat berupa kendala teknis maupun non teknis. Di antara sejumlah kendala teknis, aspek agronomi seperti kebiasaan petani menggunakan tajar pendek (+3.0 m), pemupukan dan pemangkasan yang tidak optimal diduga kuat berkontribusi terhadap masih rendahnya capaian tersebut. Penggunaan tajar tinggi (> 5 m) disertai pemangkasan optimal, baik terhadap tanaman pokok lada maupun tajar hidupnya sangat berpotensi meningkatkan produktivtas rata-rata lada nasional lebih dari 1,5 ton/ha/th. Produksi dan produktivitas lada nasional diharapkan dapat lebih besar lagi apabila disertai penerapan aspek budidaya menanam lada lebih dari satu pohon per tajar. Sosialisasi dan penerapan ketiga aspek budidaya lada tersebut pada tingkat lapang secara terencana dan berkesinabungan diharapkan dapat meningkatkan produksi dan produktivitas lada nasional.Kata kunci: Lada, produktivitas, tajar hidup, pemang-kasanABSTRACTStrategy in Increase Productivity of Black Pepper With High Supports, Intensified Pruning and Its Adoption Possibility in IndonesiaBlack pepper is an important and traditional export commodity of Indonesia. The mean productivity of Indonesian black pepper is low (< 1 ton/ha) which is much lower than those of other producing countries such as Vietnam, Brazil and Malaysia. There are number factors influencing the low productivity of black pepper vines in the country, both technical and non-technical constraints. Among them, agronomic aspects such as the use of short supports or standards of about + 3.0 m in height, and unintensified pruning of both black pepper vines and its live supports are believed to contributing low in yields of the crop. In other words, the use of live supports with height of more than 5.0 m, followed by intensified pruning of black pepper vines and its live supports are able to increase the mean national productivity of the crop of higher than of 1,5 tons ha/year. Higher in yields or productivity of black pepper vine may be achieved if farmers not only adopt the two agronomic aspects but also other recommended cultural practices do. Hence, socialization and implementation of the improved cultural practice technologies for the crop is needed in the future, in turn, higher in yield or productivity of the crop as well as income of farmers be achieved.Keywords: Black pepper, productivity, live supports, pruning